Clonal propagation characteristics of woody species in Baishanzu broad-leaved evergreen forest - CHEN Jiao; WANG Wei; YE Zhen-lin; CHEN Xiao-hui; JIANG Qing-ling; DING Bing-yang (浙江大学学报. 农业与生命科学版, 2012)
Clonal plants, which are generated through both sexual reproduction and vegetative propagation (clonal growth) in nature, can affect species distribution patterns and dynamics, as well as the species composition and diversity of communities. Clonal plants with ability to adapt to the harsh environment have strong competence for survival, and thus play an important role in regeneration and revegetation of the forest dynamics. Based on the investigation of the root-sprouting situation of shrubs and woody vines with DBH (diameter at breast height) ≥ 1 cm or height ≥ 2 m and trees in Baishanzu permanent plot, the objective of this study was to research the sprouting ability of different species with different growth forms, the relationship between root-sprouting rate and DBH of parent-ramet and the association between sprouting rate and habitats.A 5-hm2 plot in Baishanzu Mountain was divided into 2 000 quadrats (5 m × 5 m) to survey species identity, DBH, root-sprouting number and root-sprouting DBH / basal diameter for shrubs and woody vines with DBH ≥ 1 cm and all trees. Species in the plot were classified into canopy trees, sub-canopy trees, understory trees, shrubs and vines to survey the differences of their root-sprouting capacity. The relationship between root-sprouting rate and DBH of parent-ramet was analyzed based on six common species with the number of mother plant ≥ 400 and root-sprouting rate ≥ 1.0. According to the differences of slope, convexity and elevation among quadrates, the plot was divided into four habitats, including ridge, less-steep slope, steep slope and gully to analyze the association between sprouting rate and habitats.The results showed that: 1) The total parent-ramet and sprout in the plot were 36 769 and 34 786 respectively, thus the sprouting rate of the species in the plot was 0.94 (Table 1); 2) the sprouting rates of species with different growth forms were different with the descending order of canopy species, sub-canopy species, understory species, shrubs and vines (Table 1); 3) twelve species according with the mother plant numbers ≥ 200 and root-sprouting rate ≥ 0.50 belonged to the dominant species from canopy, sub-canopy, understory and shrub species (Table 2); 4) the sprouting rates were positively related to the DBH of the parent-ramet for all species together or six main species, respectively. At the same time, the maximum values of the sprouting rate were responded to the DBH values which were slightly larger than the intermediate values of DBH for all species (Fig. 2, 3); 5) the sprouting rates and sprout density in four habitats in the plot were different, and the sprouting rates and parent-ramet density were both descended with the order of ridge, less-steep slope, steep slope, gully (Table 3).In conclusion, the relatively high sprouting rate in the plot indicates that the clonal reproduction is an important reproduction strategy for woody plants in the communities; the generally high sprouting rate of the dominant species from canopy trees, sub-canopy trees, understory trees and shrubs indicates that the clonal reproduction plays an important role in the formation of forest community structure; the positive relationship between the parent-ramet DBH and root-sprouting rate reflects that the growth and ecesis of root-sprouting depend on resource supplement from the parent-ramet; meanwhile, the relationship between sprouting rates and habitat is consistent with the risk-sharing principle of the clonal plant genets.